2018
DOI: 10.12741/ebrasilis.v11i2.759
|View full text |Cite
|
Sign up to set email alerts
|

Borboletas (Lepidoptera: Papilionoidea e Hesperioidea) da Reserva Biológica do Gurupi, Maranhão, Brasil

Abstract: Resumo. As borboletas constituem um dos grupos mais utilizados em estudos de monitoramento e mensuração do equilíbrio ambiental, uma vez que são sensíveis a qualquer tipo de alteração ambiental. O objetivo do presente estudo é divulgar a primeira lista de espécies de borboletas da REBIO do Gurupi e estimar a representatividade dessas espécies na comunidade. Foram realizadas coletas bimestrais, durante sete dias consecutivos, entre jan/2010 e jul/2011. Os espécimes foram obtidos com uso de rede entomológica e a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 6 publications
0
6
0
7
Order By: Relevance
“…Some studies have suggested that Jackknife1 and Chao1 estimators are quite efficient to estimate the number of butterfly species with a greater sampling effort as in Lima & Zacca (2014) and Pereira et al (2018).…”
Section: Species Accumulation Curvementioning
confidence: 99%
“…Some studies have suggested that Jackknife1 and Chao1 estimators are quite efficient to estimate the number of butterfly species with a greater sampling effort as in Lima & Zacca (2014) and Pereira et al (2018).…”
Section: Species Accumulation Curvementioning
confidence: 99%
“…Although approximately 3,500 species of butterflies are documented in Brazil (Mielke et al 2021;Carneiro 2021;leviski & Casagrande 2021;duarte & robbins 2021;Dolibaina et al 2021;Lourido & Duarte 2021), the knowledge on this group of insects is heterogeneous, with most inventories carried out in the south and southeast regions of the country (santos et al 2008). One of the first lists of butterflies for the northeast region of Brazil was provided by bates (1867), followed by some works carried out in the 20th century (D'alMeida 1935;CarvalHo & CarvalHo 1939, 1941Cardoso 1949;CarvalHo & Freitas 1960;Alvarenga 1962;Silva 1967;Kesselring & Ebert 1979;GarCia et al 1990) with an substantial increase in recent decades (Freitas 2003(Freitas , 2004Nobre et al 2008;VasConCelos et al 2009;ZaCCa 2009;ZaCCa et al 2011;PaluCH et al 2011PaluCH et al , 2016Nobre et al 2012;ZaCCa & Bravo 2012;Kerpel et al 2014;LiMa & ZaCCa 2014;Martins et al 2017;Rafael et al 2017;Pereira et al 2018;Melo et al 2019;VasConCelos et al 2019;.…”
Section: Entomobrasilis 14: E959 (2021)mentioning
confidence: 99%
“…Nos últimos anos, levantamentos também foram conduzidos na porção nordestina da Amazônia em áreas de transição entre a Amazônia e o Cerrado no Maranhão e também no maior remanescente da Floresta Amazônica do estado PEREIRA et al, 2018). O inventário da Reserva Biológica do Gurupi, MA realizado por Pereira et al (2018) registrou 91 spp.…”
Section: Inventários De Borboletas (Papilionoidea) No Nordeste Do Brasilunclassified